Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan pada PT Tiga Berlian Mandiri Surabaya - Devi Liliana Putri Marfida; Iswati Iswati; Eny Sulistyowati (Journal Economic Excellence Ibnu Sina, 2024)
This study aims to further investigate "The Influence of Service Quality and Price on Customer Satisfaction" at PT Tiga Berlian Mandiri Surabaya. The background of this research is that in the era of globalization, customer satisfaction becomes a key success factor for companies to continue to grow and compete. PT. Tiga Berlian Mandiri (Tiberman), an importer of heavy equipment tires, has faced complaints related to customer dissatisfaction due to service issues. This is also supported by company data showing a decline in April 2024. Therefore, this research is important to help the company improve the services and products provided. The objectives of this study are to determine: the influence of service quality on customer satisfaction, the influence of price on customer satisfaction, and the influence of both service quality and price on customer satisfaction. The method used in this research is the quantitative method, which aims to develop mathematical models, theories, and hypotheses related to a phenomenon to determine the relationships between variables within a population. Data were obtained through observation, questionnaires, and literature studies. The research population is the employees and customers of PT Tiga Berlian Mandiri Surabaya, with a sample of 34 taken from the population using purposive sampling technique. The questionnaire results were calculated using a Likert Scale. The conclusion of this study is that service quality affects customer satisfaction and price affects customer satisfaction.